Internalization of Mutual Cooperation Values in Pancasila Student Profile Curriculum in Indonesian Senior High School - Wati, Ratu Suci Sholikhah; Saputra, Meidi (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2025)
This research aims to describes the implementation of Pancasila Student Profile Strengthening Project (P5), the internalization of the value of cooperation in P5, and supporting and inhibiting factors. The method used is descriptive qualitative, data sources, including informants, events, and documents. Data collection was conducted based on observation, interviews and documentation. Data validity used triangulation sources, techniques, and theories, while data analysis included data reduction, data presentation, and verification. The research results show that the implementation of P5 involved planning through a joint meeting to form a team of designers and developers of the P5 module; the implementation was conducted daily within 3-4 months, and evaluation took place conditionally, twice or thrice each semester. Second, The internalization of the value of cooperation involved value transformation stages through dialogue with students; value transactions included telling stories about project success and group formation, trans-internalization was performed by getting used to group work. Third, supporting factors in the internalization of the value of cooperation involve the cooperative attitude of the students in learning P5, assistance given by teachers and parents, and good school infrastructure. However, this study also discovered some inhibiting factors. This research contributes to the broader discourse on character education in Indonesia by offering a grounded example of how national values can be internalized through innovative educational programs like P5. Further studies are recommended to explore the scalability and long-term impact of such initiatives across diverse educational contexts.